![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(70-\left(x-3\right)=45\)
\(x-3=70-45\)
\(x-3=25\)
\(x=25+3\)
\(x=28\)
b) \(12+\left(5+x\right)=20\)
\(5+x=20-12\)
\(5+x=8\)
\(x=8-5\)
\(x=3\)
c) \(130-\left(100+x\right)=25\)
\(100+x=130-25\)
\(100+x=105\)
\(x=105-100\)
\(x=5\)
d) \(175+\left(30-x\right)=200\)
\(30-x=200-175\)
\(30-x=25\)
\(x=30-25\)
\(x=5\)
e) \(\left(x+12\right)+22=92\)
\(x+12=92-22\)
\(x+12=70\)
\(x=70-12\)
\(x=58\)
f) \(95-\left(x+2\right)=45\)
\(x+2=95-45\)
\(x+2=50\)
\(x=50-2\)
\(x=48\)
a)
70 - (x - 3) = 45
x - 3 = 70 - 45 = 25
x = 25 + 3 = 28
Vậy x = 28
b)
12 + (5 + x) = 20
5 + x = 20 - 12 = 8
x = 8 - 5 = 3
Vậy x = 3
c)
130 - (100 + x) = 25
100 + x = 130 - 25 = 115
x = 115 - 100 = 15
Vậy x = 15
d)
175 + (30 - x) = 200
30 - x = 200 - 175 = 25
x = 30 - 25 = 5
Vậy x = 5
e)
(x + 12) + 22 = 92
x + 12 = 92 - 22 = 70
x = 70 - 12 = 58
Vậy x = 58
f)
95 - (x + 2) = 45
x + 2 = 95 - 45 = 50
x = 50 - 2 = 48
Vậy x = 48
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(70-5\left(x-3\right)=45\)
\(5\left(x-3\right)=25\)
\(x-3=5\)
\(\Rightarrow x=8\)
b) \(12+\left(5+x\right)=20\)
\(5+x=8\)
\(\Rightarrow x=3\)
c) \(130-\left(100+x\right)=25\)
\(100+x=105\)
\(\Rightarrow x=5\)
d) \(175+\left(30-x\right)=200\)
\(30-x=25\)
\(\Rightarrow x=5\)
e) \(5\left(x+12\right)+22=92\)
\(5\left(x+12\right)=70\)
\(x+12=14\)
\(\Rightarrow x=2\)
a. 70 - 5.(x - 3) = 45
5.(x - 3) = 70 - 45
x - 3 = 25 : 5
x = 5 + 3
x = 8
b. 12 + (5 + x) = 20
5 + x = 20 - 12
x = 8 - 5
x = 3
c. 130 - (100 + x) = 25
100 + x = 130 - 25
x = 105 - 100
x = 5
d. 175 + (30 - x) = 200
30 - x = 200 - 175
x = 30 - 25
x = 5
e. 5.(x + 12) + 22 = 92
5.(x + 12) = 92 - 22
x + 12 = 70 : 5
x = 14 - 12
x = 2
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\left|x-1\right|=5\)
<=> \(\hept{\begin{cases}x-1=5\\x-1=-5\end{cases}}\)
<=> \(\hept{\begin{cases}x=6\\x=-4\end{cases}}\)
\(x^2=25\)
<=> \(\hept{\begin{cases}x=5\\x=-5\end{cases}}\)
\(3\left(x-2\right)=5\left(x+1\right)\)
<=> \(3x-6=5x+5\)
<=> \(-2x=11\)
<=> \(x=\frac{-11}{2}\)
\(3x+5^{94}:5^{92}=3^2+8\)
<=> \(3x+25=9+8\)
<=> \(3x=-8\)
<=> \(x=\frac{-8}{3}\)
\(a)|x-1|=5\)
\(\Leftrightarrow\hept{\begin{cases}x-1=5\\x-1=-5\end{cases}}\)
\(\Leftrightarrow\hept{\begin{cases}x=6\\x=-4\end{cases}}\)
\(b)x^2=25\)
\(\Leftrightarrow\hept{\begin{cases}x=5\\x=-5\end{cases}}\)
\(c)3\times\left(x-2\right)=5\times\left(x+1\right)\)
\(\Leftrightarrow3x-6=5x+5\)
\(\Leftrightarrow-2x=11\)
\(\Leftrightarrow x=\frac{-11}{2}\)
\(d)3\times x+5^{94}\div5^{92}=3^2+8\)
\(\Leftrightarrow3x+25=9+8\)
\(\Leftrightarrow3x=-8\)
\(\Leftrightarrow x=\frac{-8}{3}\)
( 70 + x ) + 8.9 = 92
( 70 + x ) + 72 = 92
70 + x = 92 - 72
70 + x = 20
x = 20 - 70
x = -50
2( 70 + x ) + 8.9 = 92
2( 70 + x ) + 72 = 92
2( 70 + x ) = 92 - 72
2(70 + x ) = 20
70 + x = 20 : 2
70 + x = 10
x = 10 - 70
x = -60